Quadrivalent Influenza Vaccine Prevents Illness and Reduces Healthcare Utilization Across Diverse Geographic Regions During Five Influenza Seasons: A Randomized Clinical Trial. Issue 1 (January 2020) - Dbaibo, Ghassan; Amanullah, Arshad; Claeys, Carine; Izu, Allen; Jain, Varsha K.; Kosalaraksa, Pope; Rivera, Luis; Soni, Jyoti; Yanni, Emad; Zaman, Khalequ; Acosta, Beatriz; Ariza, Miguel; et al.
Abstract : Background: We evaluated an inactivated quadrivalent influenza vaccine (IIV4) in children 6–35 months of age in a phase III, observer-blind trial. Methods: The aim of this analysis was to estimate vaccine efficacy (VE) in preventing laboratory-confirmed influenza in each of 5 independent seasonal cohorts (2011−2014), as well as vaccine impact on healthcare utilization in 3 study regions (Europe/Mediterranean, Asia-Pacific and Central America). Healthy children were randomized 1:1 to IIV4 or control vaccines. VE was estimated against influenza confirmed by reverse transcription polymerase chain reaction on nasal swabs. Cultured isolates were characterized as antigenically matched/mismatched to vaccine strains. Results: The total vaccinated cohort included 12, 018 children (N = 1777, 2526, 1564, 1501 and 4650 in cohorts 1−5, respectively). For reverse transcription polymerase chain reaction confirmed influenza of any severity (all strains combined), VE in cohorts 1−5 was 57.8%, 52.9%, 73.4%, 30.3% and 41.4%, respectively, with the lower limit of the 95% confidence interval >0 for all estimates. The proportion of vaccine match for all strains combined in each cohort was 0.9%, 79.3%, 72.5%, 24.1% and 28.6%, respectively. Antibiotic use associated with influenza illness was reduced with IIV4 by 71% in Europe, 36% in Asia Pacific and 59% in Central America. Conclusions: IIV4 prevented influenza in children 6−35 months of age in each of 5 separate influenza seasons in diverse geographical regions. A possible interaction between VE, degree of vaccine match and socioeconomic status was observed. The IIV4 attenuated the severity of breakthrough influenza illness and reduced healthcare utilization, particularly antibiotic use. Abstract : Supplemental Digital Content is available in the text.